Comparison of meat quality attributes of improved native chicken varieties Vanaraja and Indbro with Commercial broiler chicken - S, Sneha Priya; M, Shashi Kumar; M , Muthu Kumar; A, Vijaya Kumar (Journal of Meat Science, 2023)
There is great demand for native chicken meat due to its unique strong  flavour, firm and hard texture and lower fat content and fetches almost  thrice the price of broiler meat. During the last few years, improved native  chicken varieties are being introduced to meet the demand and the market  share is steadily increasing. The present study was conducted to compare the  carcass characteristics and meat quality attributes of improved native chicken  varieties viz., Vanaraja (dual purpose chicken) and Indbro (slow growing  coloured broiler) with Commercial broilers. In this study, total of 30 birds,  comprising 10 birds each from Vanaraja (56 days old), Indbro (49 days old),  and Commercial broilers (38 days old) at their respective marketable age  were selected for evaluation. Analysis of carcass traits revealed significantly  (P
Keywords: Meat Quality; Improved native chicken breeds; Commercial broiler chicken; Comparison